Sex difference in circulating PCSK9 and its clinical implications - Jia, Fang; Fei, Si-Fan; Tong, De-Bing; Xue, Cong; Li, Jian-Jun (Frontiers in Pharmacology, 2022)
Proprotein convertase subtilisin kexin type 9 (PCSK9) is a proprotein convertase that increases plasma low-density lipoprotein cholesterol (LDL-C) levels by triggering the degradation of LDL receptors (LDLRs). Beyond the regulation of circulating LDL-C, PCSK9 also has direct atherosclerotic effects on the vascular wall and is associated with coronary plaque inflammation. Interestingly, emerging data show that women have higher circulating PCSK9 concentrations than men, suggesting that the potential roles of PCSK9 may have different impacts according to sex. In this review, we summarize the studies concerning sex difference in circulating levels of PCSK9. In addition, we report on the sex differences in the relations of elevated circulating PCSK9 levels to the severity and prognosis of coronary artery disease, the incidence of type 2 diabetes mellitus, and neurological damage after cardiac arrest and liver injury, as well as inflammatory biomarkers and high-density lipoprotein cholesterol (HDL-C). Moreover, sex difference in the clinical efficacy of PCSK9 inhibitors application are reviewed. Finally, the underlying mechanisms of sex difference in circulating PCSK9 concentrations and the clinical implications are also discussed.